Analisis Kesuksesan Aplikasi Mobile Pemesanan Tiket Bioskop M-Tix Cinema 21 Berdasarkan Perspektif Pengguna di Kota Malang Menggunakan Pendekatan Delone and McLean Success Model - Yugo Fairnando Augusto; Aditya Rachmadi; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
M-Tix Cinema 21 mobile app offers online cinema ticket booking service for Cinema 21 network throughout Indonesia. However, in operation there are still some complaints submitted by users for this application. In addition, in Malang City M-Tix Cinema 21 mobile app is still underutilized by the public. Based on the results of the preliminary survey, the percentage of respondents who has used this application to booked cinema tickets in Malang City was only 32.4%. The objective of the study was to describe the success rate of M-Tix Cinema 21 mobile app and provide recommendation improvements based on the concept of DeLone and McLean Success Model. Data collection was done by distributing questionnaires, where the number of samples in this study was 112 people and selected using Purposive Sampling technique. The results of this study indicated that the success rate of M-Tix Cinema 21 mobile application on System Quality variables belongs into high category (75.8%), and Use variables belongs into the high category (75.0%). Based on the comparison of each variables mean percentage, Use variables are prioritized to get improvement recommendations. Recommendations that can be given both to improved System Quality variables and Use variables such as by performing system maintenance periodically and improving marketing strategy of M-Tix Cinema 21 mobile application.